Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10461-015-1245-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Community-Based Exercise Program on Inflammation, Metabolic Risk, and Fitness Levels Among Persons Living with HIV/AIDS

Abstract: The human immunodeficiency virus (HIV) pandemic remains a top national health priority. Chronic inflammation may be a critical component in the disease course of HIV as C-reactive protein (CRP) is elevated and associated with increased mortality. This study examined the effect of 3 months of combined aerobic and resistance exercise training among a diverse cohort of HIV-infected men and women. The fixed effect of time for CRP was found to be non-significant (F[1,57.3] = 1.7, p = 0.19). There was a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
2
17
1
Order By: Relevance
“…Our finding that moderate (∼7%) weight loss improves skeletal muscle insulin sensitivity, assessed as insulin‐mediated glucose disposal rate during insulin infusion, differs from the results of a previous study that found a 7% weight loss achieved by dietary modification and physical activity failed to improve insulin sensitivity, assessed by using the frequently sampled intravenous glucose tolerance test . The results from two other studies found that lifestyle therapy in patients with HIV infection resulted in a decrease in waist circumference without a change in body weight but failed to show any beneficial metabolic benefits . The reason for the different findings between our study and the previous study that found weight loss in HIV+ patients did not improve insulin sensitivity could be related to differences in cART regimens and in the methods used to assess insulin action.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that moderate (∼7%) weight loss improves skeletal muscle insulin sensitivity, assessed as insulin‐mediated glucose disposal rate during insulin infusion, differs from the results of a previous study that found a 7% weight loss achieved by dietary modification and physical activity failed to improve insulin sensitivity, assessed by using the frequently sampled intravenous glucose tolerance test . The results from two other studies found that lifestyle therapy in patients with HIV infection resulted in a decrease in waist circumference without a change in body weight but failed to show any beneficial metabolic benefits . The reason for the different findings between our study and the previous study that found weight loss in HIV+ patients did not improve insulin sensitivity could be related to differences in cART regimens and in the methods used to assess insulin action.…”
Section: Discussioncontrasting
confidence: 99%
“…After screening titles and application of the eligibility criteria, 21 studies (Baigis et al, 2002;Cade et al, 2003;Cade et al, 2013;Cutrono et al, 2015;Dolan et al, 2006;Ezema et al, 2014;Hand et al, 2008;Jaggers et al, 2014;MacArthur et al, 1993;Mangona et al, 2015;Mapstone et al, 2014;Mutimura et al, 2008;Neto et al, 2016;Oursler et al, 2009;Perna et al, 1999;Ramírez-Marrero et al, 2014;Raso et al, 2013;Smith et al, 2001;Sullivan et al, 2014;Terry et al, 2006;Thoni et al, 2002) were eligible for inclusion in the meta-analysis. (n=31) and sub-maximal (n=5) exercise tests.…”
Section: Search Results and Flow Of Studies Through The Reviewmentioning
confidence: 99%
“…[ 39 ] Yet there is evidence that HIV-infected adults are less likely to meet even these recommendations compared to the general population. [ 40 ] Furthermore, recent exercise trials in HIV-infected adults suggest that exercise intensity[ 41 ] and loss of body fat[ 42 ] are important predictors to reduce inflammation. Our preliminary findings need to be confirmed in a larger trial with a more diverse population.…”
Section: Discussionmentioning
confidence: 99%